Ramona's world - Cleary, Beverly; Dockray, Tracy (New York : HarperTrophy, 2006)
Ramona Quimby expects fourth grade to be the best year of her life; and although things do not go just as she had hoped, she still manages to have her share of adventures.
Booklist starred.
School Library Journal.
Wilson's Children.
Booklist starred, June 1999.
Bulletin (Center for Children's books), September 1999.
Horn Book, September 1999.
Keywords: Families -- Juvenile fiction; Quimby, Ramona (Fictitious character) -- Juvenile fiction; Schools -- Juvenile fiction; Family life -- Fiction; Quimby, Ramona (Fictitious character) -- Fiction; Schools -- Fiction; Family life -- Fiction; Quimby, Ramona (Fictional character) -- Fiction; School stories